Classification of physical status and anesthetic risk of dogs submitted to osteosynthesis - Maia, Luan Vinicius Tezzei; de Franca, Andressa Gavassi; Sala, Pollyana Linhares; de Sa, Thais Camaso; Trentim, Mayara da Silva; Quessada, Ana Maria (Seven Editora, 2023)
The main case series of orthopedic problems in veterinary clinics of small animals are fractured by traumatic events (SHIJU et al., 2010). The fact that fractures occur more in young animals is probably related to bone fragility characteristics of the age group because they are in the growth phase. In addition, young dogs cannot avoid trauma (VIDANE et al., 2014). Every patient who needs to undergo a surgical procedure is highly indispensable to perform a preoperative evaluation with anamnesis, physical examination, and complementary before being submitted to anesthesia. This evaluation reduces the risk of complications during the surgical procedure and also decreases the rate of post-surgical deaths (SCHWARTZMAN et al., 2011). The classification according to the American Society of Anesthesiologists (ASA, 2014) of patients who will undergo surgical procedures has become an important tool to ensure safety (SCHWARTZMAN et al., 2011). Thus, this classification should be included in the patient’s clinical form, thus allowing for to minimize of possible complications during the surgical and anesthetic procedure, providing more efficiently the real prognosis of the patient (LUZ et al., 2012). DOI: https://doi.org/10.56238/methofocusinterv1-069